2015
DOI: 10.1007/s11606-015-3547-4
|View full text |Cite
|
Sign up to set email alerts
|

Provider-to-Provider Communication during Transitions of Care from Outpatient to Acute Care: A Systematic Review

Abstract: BACKGROUND: Most research on transitions of care has focused on the transition from acute to outpatient care. Little is known about the transition from outpatient to acute care. We conducted a systematic review of the literature on the transition from outpatient to acute care, focusing on provider-to-provider communication and its impact on quality of care. METHODS: We searched the MEDLINE, CINAHL, Scopus, EMBASE, and Cochrane databases for English-language articles describing direct communication between outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
(103 reference statements)
0
20
0
1
Order By: Relevance
“…The authors also found that when communication did occur, the communication was most often telephone-based, potentially limiting the amount of data transferred. [27] Thus, until electronic health record data sharing improves, it may be reasonable to consider screening for select risk factors such as psychosocial barriers during hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that when communication did occur, the communication was most often telephone-based, potentially limiting the amount of data transferred. [27] Thus, until electronic health record data sharing improves, it may be reasonable to consider screening for select risk factors such as psychosocial barriers during hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Several components have been identified which are felt to be key in reducing adverse events as patients move from one level or setting of care to another. As electronic health records have become the primary tool for documenting and storing patient information, they can facilitate the timely sharing of information required for continuity of care [109]. The primary mode of communication with the highest rates of direct transfer of patient information from one provider to another occurs via telephonic communication, with successful communication occurring approximately 70% of the time [110].…”
Section: Ameliorate High-risk Error Areas Such As Transitions Of Carementioning
confidence: 99%
“…The paper by Luu et al 5 systematically examines the literature on provider-to-provider communication during transitions from outpatient to acute care. The major finding is that the research landscape is relatively barren, with only three randomized controlled trials evaluating the relationship between communication quality and 30-day readmission rates.…”
mentioning
confidence: 99%